Dynamics of CXCR4 positive circulating tumor cells in prostate cancer patients during radiotherapy. Issue 12 (13th March 2023) - Klusa, Daria; Lohaus, Fabian; Franken, Andre; Baumbach, Marian; Cojoc, Monica; Dowling, Paul; Linge, Annett; Offermann, Anne; Löck, Steffen; Hušman, Dejan; Rivandi, Mahdi; Polzer, Bernhard; et al.
Abstract: Ablative radiotherapy is a highly efficient treatment modality for patients with metastatic prostate cancer (PCa). However, a subset of patients does not respond. Currently, this subgroup with bad prognosis cannot be identified before disease progression. We hypothesize that markers indicative of radioresistance, stemness and/or bone tropism may have a prognostic potential to identify patients profiting from metastases‐directed radiotherapy. Therefore, circulating tumor cells (CTCs) were analyzed in patients with metastatic PCa (n = 24) during radiotherapy with CellSearch, multicolor flow cytometry and imaging cytometry. Analysis of copy‐number alteration indicates a polyclonal CTC population that changes after radiotherapy. CTCs were found in 8 out of 24 patients (33.3%) and were associated with a shorter time to biochemical progression after radiotherapy. Whereas the total CTC count dropped after radiotherapy, a chemokine receptor CXCR4‐expressing subpopulation representing 28.6% of the total CTC population remained stable up to 3 months. At once, we observed higher chemokine CCL2 plasma concentrations and proinflammatory monocytes. Additional functional analyses demonstrated key roles of CXCR4 and CCL2 for cellular radiosensitivity, tumorigenicity and stem‐like potential in vitro and in vivo. Moreover, a high CXCR4 and CCL2 expression was found in bone metastasis biopsies of PCa patients. In summary, panCK + CXCR4 + CTCs may have a prognostic potential in patients with metastatic PCa treated with metastasis‐directed radiotherapy. Abstract : What's new? Some patients with prostate cancer (PCa) do not respond to radiotherapy, but there is not yet a way to identify which patients will progress. Here, the authors analyzed circulating tumor cells (CTCs) in patients with metastatic, progressive PCa at three time points during radiotherapy. While total CTC count dropped after radiotherapy, they identified a subpopulation of CTCs that expressed the chemokine receptor CXCR4 whose numbers remained stable up to three months. This cell type was associated with metastatic spread, and may provide a way to dynamically monitor patients during therapy and identify those who are most likely to progress.